2002
DOI: 10.1002/jmri.10142
|View full text |Cite
|
Sign up to set email alerts
|

Radial fast spin‐echo method for T2‐weighted imaging and T2 mapping of the liver

Abstract: Purpose: To evaluate a multishot radial fast-spin echo (RAD-FSE) method developed to improve the quality of abdominal T2-weighted imaging as well as the characterization of focal liver lesions. Materials and Methods:The RAD-FSE sequence used in this work consisted of a preparatory period followed by a short echo train (ETL ϭ 16). A novel radial k-space trajectory was used to minimize streaking artifacts due to T2 variations and motion. Small diffusion gradients (b ϭ 1.2 mm/s 2 ) were used to improve flow suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 41 publications
4
85
1
Order By: Relevance
“…The method is fast (in the case of body applications, data can be acquired in a breath hold) and since the TE images are generated from a single k-space data set, misregistration problems are minimized. We have shown that this methodology can be used to measure T 2 s in patients with focal liver lesions and successfully characterize lesions as benign or malignant (13). However, as was pointed out in our initial work, there are artifacts in the T 2 maps due to the mixing of TE data in the reconstruction process.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The method is fast (in the case of body applications, data can be acquired in a breath hold) and since the TE images are generated from a single k-space data set, misregistration problems are minimized. We have shown that this methodology can be used to measure T 2 s in patients with focal liver lesions and successfully characterize lesions as benign or malignant (13). However, as was pointed out in our initial work, there are artifacts in the T 2 maps due to the mixing of TE data in the reconstruction process.…”
mentioning
confidence: 71%
“…Recently it was shown that high resolution images at various effective TE (TE eff ) values can be generated from a single radial fast spin-echo k-space data set (12,13). This is achieved by using data acquired at a specific TE (or narrow TE range) at the center of k-space and all the radial data in the outer part of k-space.…”
mentioning
confidence: 99%
“…7). Two-dimensional prospective acquisition correction (PACE) [13][14][15][16][17][18] is the other solution. It is important to select the most suitable method for the patient depending on his W her status.…”
Section: Respiratory Motionmentioning
confidence: 99%
“…The coarsely sampled k-space periphery is filled by all other single-echo data sets. In addition, motion-induced ar-tifacts can by minimized by an appropriate view-ordering scheme that distributes sequentially acquired echotrains over radians (20) so that adjacent views experience different motion kinetics. However, this would hamper an appropriate phase correction that presupposes that the difference in the linear phases of adjacent projections evolves solely from system latencies.…”
Section: Discussionmentioning
confidence: 99%